Analisis buku ajar fisika SMA kelas XI berdasarkan pada komponen literasi era digital - Deby Putri Perwita; Yesni Oktrisma; Popi Sri Kandika; Asrizal Asrizal (Universitas Negeri Padang, 2019)
The purpose of this study is to analyze Physics textbooks used in Padang based on digital age literacy content. The study analyzed the books based on the contents of aspects of digital age literacy, namely (1) Scientific literacy, (2) information literacy, (3) and visual literacy. The object of this study is the high school physics textbook. The study population was all material in 5 high school physics textbooks analyzed. The initial step in this research is to conduct a survey of high school physics class XI textbooks used in Padang City. The schools surveyed were chosen randomly. The next step is to choose five textbooks that have been approved by the Book Center and are the most widely used by students and teachers in schools in the Padang region. The books analyzed were 5 books from different publishers. Furthermore, this book is labeled with books A, B, C, D and E. The results of analysis of high school physics textbooks obtained that in book A the percentage of emergence was 57%, Book B% 56%, Book C 38%, Book D 71% and E book 78%. Class XI high school physics textbooks analyzed already contain categories of digital literacy, so teachers can use physics literacy materials containing digital literacy and can be used by students in learning, but in book C they do not include digital literacy categories due to the low aspects of scientific literacy, information literacy and literacy visually so book B is not yet suitable for use as teaching material